2018
DOI: 10.3758/s13428-018-1048-1
|View full text |Cite
|
Sign up to set email alerts
|

The EU-Emotion Voice Database

Abstract: In this study, we report the validation results of the EU-Emotion Voice Database, an emotional voice database available for scientific use, containing a total of 2,159 validated emotional voice stimuli. The EU-Emotion voice stimuli consist of audio-recordings of 54 actors, each uttering sentences with the intention of conveying 20 different emotional states (plus neutral). The database is organized in three separate emotional voice stimulus sets in three different languages (British English, Swedish, and Hebre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
0
18
0
Order By: Relevance
“…The battery is based on stimuli from several sources: The face task comprised 5-s long video clips from Mindreading (www.jkp.com/mindreading) [100]. The voice and body tasks comprised 1- to 3-s long audio clips and 4- to 24-s long video clips from The EU-Emotion Stimulus Set [101, 102]. The integrative task used 3- to 19-s long sampled scenes from old television series, following Golan et al [82].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The battery is based on stimuli from several sources: The face task comprised 5-s long video clips from Mindreading (www.jkp.com/mindreading) [100]. The voice and body tasks comprised 1- to 3-s long audio clips and 4- to 24-s long video clips from The EU-Emotion Stimulus Set [101, 102]. The integrative task used 3- to 19-s long sampled scenes from old television series, following Golan et al [82].…”
Section: Methodsmentioning
confidence: 99%
“…Audio clips used neutral utterances (e.g., “what’s all this?”), spoken in appropriate emotional prosody. They were recorded in the native language on the three sites [101, 102]. In the body language clips, faces were masked, in order to prevent reliance on facial cues.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To gather suitable voice messages for testing, we explored whether there are existing datasets that contain valence and arousal ratings. The most suitable dataset is the recently published EU-Emotion Voice Database [37]. This dataset contains audio-recordings of 54 actors where stimuli are labeled with emotion expression, emotion intensity, valence, and arousal.…”
Section: Generating Neutral Voice Stimuli Eu Emotion Voice Datasetmentioning
confidence: 99%
“…This means that researchers may include or have stimuli assessed on at least one of the basic emotions, while also including/assessing further emotions (e.g. Lassalle et al, 2019;van der Schalk et al, 2011;Volkova et al, 2014;Zammuner, 2011;Zhalehpour et al, 2017). Investigating the frequency of inclusion for each of the six basic emotions revealed that happiness was included most frequently, followed by sadness, anger, fear, disgust, and surprise (see Table 10).…”
Section: Included Emotionsmentioning
confidence: 99%